Livelihood resilience and the agrifood system in Myanmar: Implications for agriculture and a rural development strategy in a time of crisis - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
Myanmar’s agrifood system has proven surprisingly resilient in the face of multiple crises—COVID 19, the military coup, economic mismanagement, global price instability, and widespread conflict—with respect to production and exports. Household welfare has not been resilient, however. High rates of inflation, especially food price inflation, have resulted in dietary degradation across all house hold groups, especially those dependent on casual wage labor. Among household members, young children experience the highest rates of inadequate dietary quality. Expanded social protection to improve access to better-quality diets for vulnerable households and individuals is therefore needed. Beyond the current political crisis, increased public and private investment in a more efficient and dynamic agrifood system should be a high priority. This will help drive down poverty rates and ensure access to healthy diets in the near term, while laying the foundation for sustained growth and struc tural transformation of the economy.